Cross-cultural adaptation and psychometric evaluation of the French version of the Gilles de la Tourette Syndrome Quality of Life Scale (GTS-QOL) - Jalenques, Isabelle; Cyrille, Diane; Derost, Philippe; Hartmann, Andreas; Lauron, Sophie; Jameux, Clara; Tauveron-Jalenques, Urbain; Guiguet-Auclair, Candy; Rondepierre, Fabien (PloS one, 2020)
The Gilles de la Tourette Syndrome-Quality of Life Scale (GTS-QOL) is a self-rated disease-specific questionnaire to assess health-related quality of life of subjects with GTS. Our aim was to perform the cross-cultural adaptation of the GTS-QOL into French and to assess its psychometric properties. The GTS-QOL was cross-culturally adapted by conducting forward and backward translations, following international guidelines. The psychometric properties of the GTS-QOL-French were assessed in 109 participants aged 16 years and above with regard to factor structure, internal consistency, reliability and convergent validity with the MOVES (Motor tic, Obsessions and compulsions, Vocal tic Evaluation Survey) and the WHOQOL-BREF (World Health Organization Quality of Life Brief). Exploratory factor analysis of the GTS-QOL-French resulted in a 6-factor solution and did not replicate the original structure in four subscales. The results showed good acceptability (missing values per subscale ranging from 0% to 0.9%), good internal consistency (Cronbach's alpha ranging from 0.68 to 0.94) and good test-retest reliability (intraclass correlation coefficients ranging from 0.70 to 0.81). Convergent validity with the MOVES and WHOQOL-BREF scales showed high correlations. Our study provides evidence of the good psychometric properties of the GTS-QOL-French. The cross-cultural adaptation and validation of this specific instrument will make it possible to assess health-related quality of life in French-speaking subjects with GTS. The GTS-QOL-French could be recommended for use in future research.